Exploring Teachers' Perspectives and Influential Factors in Math instruction for Goodhope Primary Schools - Sethukge, Shimmy; Salani, End (International Journal of Trends in Mathematics Education Research, 2024)
In this research, we delve into the perspectives of teachers and influential factors shaping math instruction in upper primary schools within the Goodhope region of Botswana. Recognizing the significance of mathematics education and the diverse learning needs of students, understanding effective teaching strategies becomes paramount. The study aims to authenticate various teaching and learning strategies employed by teachers to enhance performance in upper primary classes. The specific objectives include identifying teachers' perceptions of strategy efficacy, determining influencing factors on teaching strategies, and examining the impact of different teaching strategies on learners' performance. Guided by Critical and Constructivism theories, the research aims to uncover the nature of problems contributing to low learner performance (Critical theory) and explore engaging strategies for individual learners (Constructivism theory). The literature review underscores the study's foundation, showcasing how prior research informs the current investigation. Employing an embedded mixed methods approach, the study involved thirty teachers from ten selected schools in the Goodhope sub-region. Data collection utilized questionnaires and semi-structured interviews, while analysis employed descriptive statistics and thematic content analyses. Findings indicate that teachers employ a variety of effective teaching strategies, including incorporating games, relating mathematics to real-life situations, and using spoken and written praise. These strategies were perceived as key contributors to improving learner performance. Additionally, the study highlights the importance of satisfying learners' needs and interests for success. The recommendation emphasizes the application of diverse learner-centered teaching strategies and activities to enhance mathematics learning outcomes.